2015
DOI: 10.1130/l464.1
|View full text |Cite
|
Sign up to set email alerts
|

Timing and rates of Holocene normal faulting along the Black Mountains fault zone, Death Valley, USA

Abstract: Alluvial fans displaced by normal faults of the Black Mountains fault zone at Badwater and Mormon Point in Death Valley were mapped, surveyed, and dated using optically stimulated luminescence (OSL) and 10 Be terrestrial cosmogenic nuclide (TCN) methods. Applying TCN methods to Holocene geomorphic surfaces in Death Valley is challenging because sediment flux is slow and complex. However, OSL dating produces consistent surface ages, yielding ages for a regionally recognized surface (Qg3a) of 4.5 ± 1.2 ka at Bad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 73 publications
1
18
0
Order By: Relevance
“…We projected these extension rates (supporting information Table S1) onto the local strike of the eastern and central segments of the Garlock fault. The resulting Garlock‐parallel sinistral slip rates are 0.5–0.7 mm/year from the Death Valley fault, 0.9–1.5 mm/year from the Panamint Valley fault, and 0.1–0.2 mm/year from the Sierra Nevada Frontal fault (Frankel et al, ; Hoffman, ; Le et al, ). The maximum cumulative BR extension contribution to Garlock fault slip is therefore 1.5–2.4 mm/year, at and extending to the west of the Sierra Nevada Frontal fault (Figure ).…”
Section: Controls On Current Garlock Fault Slip Ratesmentioning
confidence: 99%
“…We projected these extension rates (supporting information Table S1) onto the local strike of the eastern and central segments of the Garlock fault. The resulting Garlock‐parallel sinistral slip rates are 0.5–0.7 mm/year from the Death Valley fault, 0.9–1.5 mm/year from the Panamint Valley fault, and 0.1–0.2 mm/year from the Sierra Nevada Frontal fault (Frankel et al, ; Hoffman, ; Le et al, ). The maximum cumulative BR extension contribution to Garlock fault slip is therefore 1.5–2.4 mm/year, at and extending to the west of the Sierra Nevada Frontal fault (Figure ).…”
Section: Controls On Current Garlock Fault Slip Ratesmentioning
confidence: 99%
“…As a consequence, if we think in terms of time‐dependent probability, these faults represent the most likely candidates for future major earthquakes in the region. Four large faults that appear not to have ruptured within the time range covered by this study are the Hunter Mountain Fault [ Oswald and Wesnousky , ], the Black Mountain Fault [ Klinger and Piety , ; Sohn et al ., ; Frankel et al ., ], the Honey Lake Fault [ Turner et al ., ], and the White Mountains Fault [ Kirby et al ., ] (Table and Figures and ). Because the most recent events on the Fish Lake Fault [ Reheis , ; Reheis et al ., ] and Pyramid Lake Fault [ Briggs and Wesnousky , ] occurred, respectively, ~1000 years and ~1300 years B.P., these two faults have also had enough time to accumulate significant values (10 to 100 bars) of ΔCFS tot .…”
Section: Discussionmentioning
confidence: 99%
“…Frankel et al . [] used optically stimulated luminescence dating to define a maximum age of ~ 4.5 ka for the most recent event on the central part of the Black Mountain Fault (Badwater site). The authors concluded that the 6.4 m tall scarp measured at the studied location could be the result of at least two surface‐rupturing events.…”
Section: Discussionmentioning
confidence: 99%
“…The slip rate of the NDVFZ is approximately 4-5 mm yr -1 averaged over the past 100 ka (Frankel et al, 2007b). For the BMFZ, the minimum normal slip rate calculated over that past 120-186 ka is 0.15-0.2 mm yr -1 (Knott and Wells, 2001), while Holocene vertical slip rates have been estimated at 1-3 mm/yr (Klinger and Piety, 2001) and 0.5-2 mm/yr (Frankel et al, 2015). Minor normal faulting also occurs along the western margin of Death Valley on the West Side Fault Zone (Machette et al, 2008).…”
Section: Settingmentioning
confidence: 99%
“…In addition, the amount of inheritance can make up a significant fraction of the total nuclide concentration in a sample, which challenges the interpretation as depositional age (Anderson et al, 1996;Hancock et al, 1999). Therefore, the amount of inheritance will have to be determined, as inheritance on alluvial fans in Death Valley can be up to 100 ka (Machette et al, 2008;Owen et al, 2011;Frankel et al, 2015). Based on a combination of field work, analysis of digital airborne swath mapping (ALSM) topographic data, and cosmogenic surface exposure dating using in-situ 10 Be and 26 Al, our goal is (a) to establish a relative and numeric age chronology on an individual alluvial fan, (b) to investigate the temporal and spatial pattern of numeric age constraints, and (c) to evaluate the time scale over which primary debris-flow morphology is removed by postdepositional fan surface modification.…”
Section: Introductionmentioning
confidence: 99%